2012
DOI: 10.4103/0028-3886.96382
|View full text |Cite
|
Sign up to set email alerts
|

An initial experience with therapeutic drug monitoring of levetiracetam as reported from a pediatric clinical setting in India

Abstract: Levetiracetam monitoring has a role in patients on antiepileptic polypharmacy and for confirmation of compliance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 10 publications
2
8
0
1
Order By: Relevance
“…In this study, the serum LEV levels (nontrough) showed a negligible negative correlation with the dose of LEV given per kilogram (kg) bodyweight. [7][8][9] Although there exists a linear relationship between the dose and the trough serum levels of LEV over a dose range of 500-5000 mg, some studies have however suggested that serum levels of LEV can get affected by a number of parameters such as age, bodyweight, comedication, hepatic, or renal insufficiency. [6] Furthermore, the LEV concentrations depend on the time interval from the last dose taken, and because of short half-life (6-8 h), large fluctuations are expected during the day; as a result, nontrough levels of LEV could not be well correlated with the dose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the serum LEV levels (nontrough) showed a negligible negative correlation with the dose of LEV given per kilogram (kg) bodyweight. [7][8][9] Although there exists a linear relationship between the dose and the trough serum levels of LEV over a dose range of 500-5000 mg, some studies have however suggested that serum levels of LEV can get affected by a number of parameters such as age, bodyweight, comedication, hepatic, or renal insufficiency. [6] Furthermore, the LEV concentrations depend on the time interval from the last dose taken, and because of short half-life (6-8 h), large fluctuations are expected during the day; as a result, nontrough levels of LEV could not be well correlated with the dose.…”
Section: Discussionmentioning
confidence: 99%
“…[9] Serum levels of LEV showed negligible positive correlation with the age of the patients as also seen by Mathew et al (r = 0.19) in their study. [7,8] Elderly patients showed higher serum LEV levels as compared to younger patients. This is in conjunction with a study conducted by May et al according to which older patients need a lower LEV dose per bodyweight than young adults to achieve comparable LEV levels.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with other AEDs, there have not been any randomized controlled trials performed with LEV to determine whether TDM improves efficacy and tolerability compared to usual care. Furthermore, a robust correlation between efficacy and plasma concentrations of LEV has not been shown in either adults or children (4)(5)(6)(7)(8). Nevertheless, variable reference ranges have been suggested with the most commonly cited one being 12-46 mg/L (9).…”
Section: Therapeutic Drug Monitoringmentioning
confidence: 99%
“…Four prospective observational studies have included LEV concentrations as part of routine monitoring but a correlation has not been noted between concentrations and efficacy or toxicity (7,(11)(12)(13). In the study by Mink et al, seizure prophylaxis with valproic acid therapy has been compared to LEV in 35 patients with aneurysmal subarachnoid hemorrhage and drug levels were taken daily (12).…”
Section: Therapeutic Drug Monitoringmentioning
confidence: 99%
“…The median serum concentration with inducers (7.30 µg/ mL) was 50% lower than for patients with inhibitors (14.40 µm/mL) and 56% lower than for patients without interfering AED co-medication (16.60 µg/ mL). The difference was statistically significant between inducers and inhibitors (P = 0.008) and between inducers and those without interfering AED co-medication (P = 0.004) [13]. These findings might be suggestive of dose adjustments of LEV, depending upon the enzyme induction/inhibition property of the co-medications.…”
Section: Drug Interactionsmentioning
confidence: 82%